2014
DOI: 10.1038/ncomms5621
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-mediated electron transfer–oxygen transfer oxidation of cellulose and hemicellulose to synthesis gas

Abstract: Terrestrial plants contain B70% hemicellulose and cellulose that are a significant renewable bioresource with potential as an alternative to petroleum feedstock for carbon-based fuels. The efficient and selective deconstruction of carbohydrates to their basic components, carbon monoxide and hydrogen, so called synthesis gas, is an important key step towards the realization of this potential, because the formation of liquid hydrocarbon fuels from synthesis gas are known technologies. Here we show that by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 32 publications
(33 reference statements)
3
51
0
Order By: Relevance
“…This stoichiometric method leads to a 65% yield of CO, which is consequently formed from FA by reaction with concentrated sulphuric acid. 24 Finally, heteropolyanion-based ionic liquids have been applied as a catalyst for cellulose conversion, leading to FA yields of 51%. 25 Summarizing the wealth of very recent studies on vanadiumcatalysed biomass oxidation, it can be stated that this transformation is characterized by its mild reaction temperature (compared to biomass gasification or hydrothermal reforming) and by its applicability to a wide range of biogenic raw materials, including non-edible biopolymers, complex biogenic mixtures and wet biomasses.…”
Section: Introductionmentioning
confidence: 99%
“…This stoichiometric method leads to a 65% yield of CO, which is consequently formed from FA by reaction with concentrated sulphuric acid. 24 Finally, heteropolyanion-based ionic liquids have been applied as a catalyst for cellulose conversion, leading to FA yields of 51%. 25 Summarizing the wealth of very recent studies on vanadiumcatalysed biomass oxidation, it can be stated that this transformation is characterized by its mild reaction temperature (compared to biomass gasification or hydrothermal reforming) and by its applicability to a wide range of biogenic raw materials, including non-edible biopolymers, complex biogenic mixtures and wet biomasses.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have reported that H 5 [V 2 Mo 10 O 40 ] catalyzes the oxidation of d-glucose and cellulose to formic acid and CO 2 with complete conversion of the substrate and yields up to 50%, working in acidic aqueous media, at 70-100 • C, in the presence of additives, like p-toluensolfonic acid, and under high O 2 pressure (20-40 bar) [59][60][61][62].…”
Section: 2-diolsmentioning
confidence: 99%
“…), and the corresponding methyl ester, formaldehyde and its derivatives (0.92 equiv.) and a minimum amount of CO 2 from over-oxidation (Scheme 7) [62].…”
Section: 2-diolsmentioning
confidence: 99%
“…These solubilized polysaccharides would be difficult to recover for ethanol production. However, this hydrolysate may be also oxidized by POMs, because POMs can function as an electron‐transfer/oxygen‐transfer catalyst for oxidation of cellulose and hemicellulose to form degradation products such as formic acid, CO, and even CO 2 depending on reaction conditions . Under the pretreatment conditions, POM oxidation of lignin mainly involves the oxidation of side chains, degradation of some inter‐unit linkages, partial degradation of the benzene structure to form benzoquinone, and removal of the aliphatic and phenolic hydroxyl groups .…”
Section: Figurementioning
confidence: 99%